And the devil makes five [large type] - Richards, Dusty (Richards, Dusty. O'Malleys of Texas, 2022)
It begins with a spectacular train robbery--a brilliantly planned, brutally executed heist masterminded by a shadowy gang of conspirators with far deadlier motives than money or gold. Their mission: to steal the train's shipment of powerful explosives. Their goal: to assassinate Mexico's legendary resistance leader Benito Juarez. As a lifelong patriot himself, Joe O'Malley understands the struggle for freedom. As a proud Texan, he knows the importance of fighting for your land and your liberty. But as patriarch of the O'Malley clan, he also believes that his family comes first--and any outsider who brings their war to his turf will have to face another deadly force of resistance...named the O'Malleys.